Experimental Study of Bond Strength of Embedded Steel Reinforcement in Vibration-Based 3D Printed Concrete Mortar - Jimmy Chandra; Alvin Halim; Franky Budiman; Pamuda Pudjisuryadi; Antoni Antoni (Institute of Research and Community Outreach - Petra Christian University, 2024)
Many new construction techniques have been developed in recent years, one of them is Three-Dimensional Concrete Printing (3DCP). It offers many advantages such as reduced human error, minimum manpower usage, and shorter construction period. This technique, however, still needs to be studied further to ensure good quality of constructions. This experimental study aims to investigate the bond strength of embedded steel reinforcement in vibration-based 3DCP mortar. The parameters varied are reinforcement diameter and direction of printing. It is found that average bond stress decreases as reinforcement diameter increases. Furthermore, 3DCP specimens with bars placed parallel to the printing direction have relatively higher bond stresses as compared to the ones with bars placed perpendicularly. As compared to conventional cast specimens, 3DCP specimens have higher bond stresses which might be due to vibration-based 3DCP mortar. Moreover, building code formulas significantly underestimate the bond stresses of vibration-based 3DCP specimens tested in this study.